Exploring the senses: South Asian and European Perspectives on Rituals and Performativity - Michaels, Axel; Wulf, Christoph (Taylor and Francis, 2013)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Exploring the Senses in Rituals and Performances: An Introduction -- Indian and Western Theories of Senses -- 1. The Windows on the World: The Senses and Inner Life -- 2. Sensory Perception and Notions of the Senses in Sāṃkhya Philosophy -- 3. Senses, Human and Divine -- 4. The Divine Embrace: The Role of the Senses in Puṣṭimārga -- 5. Managing the Senses in Sant Devotion -- The Anthropology of Senses -- 6. The Vision: Control, Desire, Perception -- 7. Seeing Ghosts in India and Europe -- 8. Sonic Perception and Acoustic Communication in Hindu India -- 9. "Noise" or "Silence?" Listening to Sacred Sound in 20th-century Europe -- 10. The Sonic Persona: An Anthropology of Sound -- 11. Taste as an Aesthetic Sense -- 12. Scent of a Flower: Notes on Olfaction in Hindu Worship -- 13. Untouchability and Tactility in Hindu Death Rituals -- 14. Senses of Movement: Kinesthetics and Synesthetics in Contemporary Dance Practices -- 15. Memory, Experience and Imagination in Performance -- 16. Family Constellation Therapy: Body Memory and the Sense of Space -- 17. Performative Ritual as Sensual Experience of Body, Place and Sociality -- The Unity of Senses -- 18. Unity of the Senses in Indian Thought -- 19. The Politics of the Senses: On Vision and Hearing in Hannah Arendt's "Vita Activa" -- 20. The Sky Around Our Bodies: Climate and Atmospheric Perception -- About the Editors -- Notes on Contributors